G970R‐CFTR Mutation (c.2908G>C) Results Predominantly in a Splicing Defect. Issue 2 (6th December 2020) - Fidler, Meredith C.; Buckley, Alexandra; Sullivan, James C.; Statia, Marvin; Boj, Sylvia F.; Vries, Robert G. J.; Munck, Anne; Higgins, Mark; Moretto Zita, Matteo; Negulescu, Paul; van Goor, Fredrick; De Boeck, Kris
Abstract : In previous work, participants with a G970R mutation in cystic fibrosis transmembrane conductance regulator ( CFTR) (c.2908G>C) had numerically lower sweat chloride responses during ivacaftor treatment than participants with other CFTR gating mutations. The objective of this substudy was to characterize the molecular defect of the G970R mutation in vitro and assess the benefit of ivacaftor in participants with this mutation. This substudy assessed sweat chloride, spirometry findings, and nasal potential difference on and off ivacaftor treatment in three participants with a G970R/F508del genotype. Intestinal organoids derived from rectal biopsy specimens were used to assess ivacaftor response ex vivo and conduct messenger RNA splice and protein analyses. No consistent or meaningful trends were observed between on‐treatment and off‐treatment clinical assessments. Organoids did not respond to ivacaftor in forskolin‐induced swelling assays; no mature CFTR protein was detected in Western blots. Organoid RNA analysis demonstrated that 3 novel splice variants were created by G970R‐CFTR : exon 17 truncation, exons 13–15 and 17 skipping, and intron 17 retention. Functional and molecular analyses indicated that the c.2908G>C mutation caused a cryptic splicing defect. Organoids lacked an ex vivo response with ivacaftor and supported identification of the mechanism underlying the CFTR defect caused by c.2908G>C. Analysis of CFTR mutations indicated that cryptic splicing was a rare cause of mutation misclassification in engineered cell lines. This substudy used organoids as an alternative in vitro model for mutations, such as cryptic splice mutations that cannot be fully assessed using cDNA expressed in recombinant cell systems.